(3cJGH aj ENJdGL GdCYVGAs - (3Ydj Hf ehSi GdcGXe Hf LYaQ GdUGOb, CHh GdMSf, GdedbH HGdQVj,J (B203 (3g` s
(3ChdgG (B:s
(3bGd LYaQ GdUGOb bGd EPG ENJdL CYVGA GdEfSGf s
(3BNQgG (B:s
(3EPG ENJdL UGHY QLdg jfGd eTbI heMfI s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B7s
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B26 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B250s
(3JHUQGJ GdCUd (B:s
(3GdfSNI eHJhQI GdBNQ s
(3eUOQ GbJfGA GdCUd (B:s
(3LGeYI eOjfI GdYde (B_ (3GdcGXejI (B(325) s
Keywords: (3GdeLGejYs